VID-THER-06: Endoscopic ultrasound-guided coiling of hepatic artery pseudoaneurysm in two stages - Prasad, Rajendra (Endosc Ultrasound, 2017)
BACKGROUND: Hepatic artery pseudoaneurysms constitute 20% of all visceral artery aneurysms. It carries very high risk of rupture with severe bleeding into peritoneal cavity, bile duct, or portal vein. Essentially, all pseudoaneurysms, whether symptomatic or not symptomatic, require early treatment to prevent lethal complications. CASE REPORT: A 20-year-old male presented with abdomen pain in the right upper quadrant for 2 months. He had undergone ultrasound-guided aspiration of liver abscess 2 months ago. Computed tomography angiography of the abdomen showed a saccular pseudoaneurysm arising from the proximal part of hepatic artery. Interventional radiologist suggested hepatic artery stenting across the neck of aneurysm and explained the associated risk of ischemia, infarction due to stent stenosis, thrombosis, and distal migration of stent. The patient chose endoscopic ultrasound (EUS)-guided coil embolization. Packing with one coil of 10 mm and five coils of 6 mm size through a 19-gauge needle caused 80% obliteration of the sac. Five days later, EUS assessment showed the injected coils were collected into the most distal part of the aneurysm, but the flow into a smaller cavity continued with high velocity. During the second attempt, four coils of 10 mm size were deployed. Postcoiling, EUS assessment still showed flow into the aneurysm. Three more coils of 8 mm size were placed and complete obliteration of aneurysm was confirmed by contrast injection and EUS. One week later, follow-up color Doppler abdomen showed no flow in the pseudoaneurysm.